FENOMENALOGIS KEBERADAAN ALLAH - ., Wahyuddin (Jurnal Pendidikan Kreatif, 2022)
God is life, he is the essence of life, if someone prefers, the essence of life is a god. Saying this we already know what God is, we know it is not through the impact of knowledge or learning, we do not know it through the mind, against the background the truth of the world, instead we know it, and can know it, only in and through life itself, we can know the essence of God only in God.This life is not a biological life that is defined by objective and external characteristics, or abstract and philosophical , but it is an absolutely phenomenal life, a radically immanent life that has the power to show itself in itself without distance, a life that expresses itself permanently. One's manifestation of oneself and self-revelation that does not consist of the reality of seeing one's outside or understanding the outside world, but in fact feelings and feelings of oneself, experiencing within oneself have inner and affective realities. As Michel Henry said in this same book, "God is a pure revelation that reveals nothing but himself. God reveals himself. God's revelation is a revelation of himself". God in himself is a revelation, he is a primordial revelation which tore everything out of nothing, a revelation which was a sad self-revelation and absolute self-enjoyment from Life. As John said, God is love, because Life loves itself in infinite and eternal love. When we live and the results are produced continually by God's infinite Life, because He never stops giving us life, and when we never stop being born into life.